Importance of microenvironment to arbovirus vector distribution in an urban area, São Paulo, Brazil - Marylene de Brito Arduino; Luis Filipe Mucci; Luciana Mamede dos Santos; Marilena Fogaça de Souza Soares (Revista da Sociedade Brasileira de Medicina Tropical, 2020)
Abstract INTRODUCTION: The study of the landscape ecology, biological microhabitat, and epidemiological implications for the distribution of the main vectors Aedes aegypti and Aedes albopictus contribute to the prevention and control actions regarding the diseases they transmit. METHODS: This study sought to assess data on positive properties of the vector control program activities from 1998 to 2010. An entomological survey was also carried out on a sample of buildings collecting larvae and pupae from containers between October and April (spring / summer) from 2002 to 2005. We assessed the physico-chemical data of the water in 20% of positive containers. The vegetation and urbanization were assessed with the aid of satellite images and microenvironments were classified as urbanized, woods, and shrubs. The data were analyzed using statistical and geoprocessing software. RESULTS: Ae. aegypti and Ae. albopictus colonized all types of microhabitats and microenvironments, predominantly in the urbanized area, in isolation and in coexistence. The microhabitat of Ae. aegypti showed a temperature gradient greater than that of Ae. albopictus, and there was an association with urbanized areas for the first species and wooded areas for the last species. CONCLUSIONS: Landscape ecology and intra-urban differences favor different microclimates, which contribute to the coexistence of species in the urban environment in an area close to the forest, raising the risk of other arbovirus infections in urban areas. The ecological niche should be considered for Ae. albopictus. Entomological and virologic monitoring are suggested as arbovirus surveillance actions in urban infested centers near preserved forests.